Adsorption of Water Vapour by Natural and Chemically Modified Clinoptilolite and Mordenite Samples - T. L. Rakytskaya; T. A. Kiose; A. S. Truba; A. A. Ennan; R. M. Dlubovskiy; V. Ya. Volkova (Хімія, фізика та технологія поверхні)
Water vapour adsorption-desorption properties of natural clinoptilolite (N–CLI) and mordenite (N?MOR) samples (Trans-Carpathian region, Ukraine), their acid modified forms, Н–CLI–6 and Н?MOR?6, and catalysts for both CO oxidation, Pd(II)-Cu(II)/Н-CLI-6 and Pd(II)-Cu(II)/Н-MOR-6, and ozone decomposition, MeCl2/N-CLI (Me = Cu, Co, Mn), have been studied. All adsorption isotherms at p/ps < 0.4 are described by BET equation with correlation coefficient R2 = 0.99. The activity of the catalysts depends on water content in samples.